Comparison of lateral abdominal muscle thickness between weightlifters and matched controls - Patraporn Sitilertpisan (2018)
Objective: To compare lateral abdominal muscle thickness between weightlifters and matched controls. Design: A case control study design. Setting: University laboratory. Subjects: 16 female Thai national weightlifters and 16 matched controls participated in this study. Main outcome measures: Ultrasound imaging with a 12-MHz linear array was used to measure the resting thickness of transversus abdominis (TrA), internal oblique (IO) and total thickness (Total) of lateral abdominal muscle (LAM) on the right side of abdominal wall. The absolute muscle thickness and the relative contribution of each muscle to the total thickness were determined. Results: Weightlifters had significantly thicker absolute TrA and IO muscles than matched controls (p < 0.01). Further, the relative thickness of the IO was significantly greater in weightlifters than matched controls (p < 0.05). Conclusions: The findings of this study suggest that routine Olympic style weight training among female weightlifters appears to result in preferential hypertrophy or adaptation of the IO muscle. © 2011 Elsevier Ltd.